EXPLORING THE EFFICACY OF ART-RELATED ACTIVITIES PARTICULARLY PAINTING AS ADJUVANT THERAPY IN SCHIZOPHRENIA: AN EVIDENCE-BASED CASE REPORT - Krisniati, Theresia Rini (Journal of Psychiatry Psychology and Behavioral Research, 2024)
Introduction – Schizophrenia is a condition that affects approximately one in 300 individuals across the globe, leading to the experience of both positive and negative symptoms. While antipsychotic medication remains the primary treatment, some patients still contend with residual symptoms and relapses. Art-related activities, particularly painting, are frequently used as potential adjuvant therapies for individuals with schizophrenia. Therefore, this study aimed to critically assess the efficacy of art-related activities, specifically painting, as supplementary therapy. Methods – A comprehensive literature search was conducted on PubMed, Google Scholar, and ScienceDirect, guided by clinical questions and strict inclusion or exclusion criteria. The selected articles were critically evaluated to determine their validity, significance, and applicability. Results – The literature search identified 3 randomized controlled trials (RCTs) and 1 case series, each with varying validity and analysis outcomes. Among the RCTs, 2 reported a positive effect of art therapy on the negative symptoms of schizophrenia, while the remaining 1 found no significant impact on patients. In a case series study, a substantial difference was observed in the symptoms of schizophrenia patients who engaged in art activities. Discuss – The 3 RCTs were done with the involvement of a licensed art therapist. The practical application of the RCT study results was still limited by the case examined since there are no art therapists in the case observed. However, in this case, the patient was observed to be more calm, cooperative and increase in ADL score after the art-related activity done in a rehabilitation program. Conclusion: There is potential for art-related activities as adjuvant therapy for individuals with schizophrenia, but it still lacks sufficient and consistent evidence.  Keywords:art, painting, therapy, schizophrenia, art-related activity.